Psychophysiology : human behavior and physiological response - Andreassi, John L. (Mahwah, N.J. : L. Erlbaum, Publishers, 2000)
"This comprehensive overview to psychophysiology provides information regarding anatomy and physiology of various body systems, methods of recording their activity, and ways in which these measures relate to human behavior. Biofeedback applications are contained in a separate chapter, and discussions of stress management, job strain, and personality factors that affect cardiovascular reactivity are presented.
There is much of interest here to the student, researcher, and clinician in behavioral medicine, ergonomics, emotion, cognitive neuroscience, neuropsychology, and health psychology."--BOOK JACKET.
14. Blood Pressure, Blood Volume, and Behavior -- 15. Applied Psychophysiology I: Detection of Deception, Vigilance, Job Design, and Workload -- 16. Applied Psychophysiology II: Auditory and Visual System Tests, Nervous System Disorders, and Behavior Disorders -- 17. Clinical Applications of Biofeedback -- 18. Concepts in Psychophysiology -- 19. Environmental Psychophysiology -- App. Laboratory Safety.
Includes bibliographical references and index.
Keywords: Psychophysiology; Psychophysiology